Pain and Sedation Management in Mechanically Ventilated Children - Sorce, Lauren; Simone, Shari (Journal of Pediatric Intensive Care, 2015)
Assessing and managing pain and agitation in critically ill children can be challenging. Multiple factors contribute to the challenges of management, including prior medication exposure, surgical and procedural interventions, pharmacokinetics, and age-related pharmacodynamics making the population heterogeneous. Therefore, individualizing treatment approaches embedded with frequent assessments is likely to improve the management of pain and agitation in critically ill children. Novel approaches to manage pain and agitation continue to evolve and will require ongoing evaluation prior to widespread adoption.
Keywords: pain; agitation; sedation; analgesia; assessment; pediatric; pediatric critical care